THE ROLE OF AROMATASE INHIBITORS IN POLYCYSTIC OVARY SYNDROME (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Polycystic Ovary Syndrome (PCOS) is one of the most common endocrine disorders affecting women of reproductive age and represents a major cause of anovulatory infertility. The syndrome is characterized by hyperandrogenism, ovulatory dysfunction, and polycystic ovarian morphology, often accompanied by metabolic disturbances such as insulin resistance and obesity. Ovulation induction remains a central component in the management of infertility associated with PCOS.